Water dance - Locker, Thomas, 1937- (San Diego, Calif. : Harcourt Brace & Company, 1997)
Water speaks of its existence in such forms as storm clouds, mist, rainbows, and rivers. Includes factual information on the water cycle.
Keywords: Water -- Fiction; Hydrologic cycle -- Fiction